Odpowiedzi

2009-11-28T13:24:53+01:00
Drugie rownanie ;

3(2x-5)-4(3y+4)=5
6x-15-12y-16=5
6x-12y=5+16+15
-6xy=36|:(-6)
xy=-6
2009-11-28T13:29:17+01:00
(x+1)/( 2y+2)=6 /*( 2y+2)
3(2x-5)-4(3y+4)=5

(x+1)=6( 2y+2)
6x-15-12y-16=5

x+1=12y+12
6x-12y=5+31

x=12y+11
6(12y+11)-12y=36

x=12y+11
72y+66-12y=36

x=12y+11
60y=36-66

x=12y+11
60y=-30

x=12y+11
y=-1/2

x=12*(-1/2)+11
y=-1/2

x=-6+11
y=-1/2

x=5
y=-1/2




2009-11-28T13:31:06+01:00
(x+1)/(2y+2)=6 /*(2y+2)
3(2x-5)-4(3y+4)=5

x+1=6(2y+2)
6x-15-12y-16=5

x+1=12y+12
6x-12y=36

x-12y=12-1
6x-12y=36

x-12y=11 /*(-1)
6x-12y=36

-x+12y=-11
6x-12y=36

5x=25 /:5
6x-12y=36

x=5
6*5-12y=36

x=5
30-12y=36

x=5
-12y=36-30

x=5
-12y=6 /:(-12)

x=5
y=-1/2